2007
DOI: 10.1080/00365520701320471
|View full text |Cite
|
Sign up to set email alerts
|

Influence of socio-economic deprivation on outcomes for patients diagnosed with oesophageal cancer

Abstract: Although deprivation was associated with younger age, SCC and a trend towards higher operative mortality, survival after diagnosis and oesophagectomy were unrelated to deprivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 26 publications
2
14
1
Order By: Relevance
“…Education has been studied more extensively in relation to survival of other types of cancer,6–10 showing a beneficial effect of higher education on survival that might be explained by the differences in comorbidity burden, lifestyle factors, health awareness, adherence to treatment and healthcare seeking behaviour, factors which are also likely to influence the timing of referral and tumour stage at diagnosis 6–10. The impact of education on survival after oesophageal cancer diagnosis has been examined in cohort studies,3 11 12 but no clear associations were found. Two studies have evaluated the influence of the socioeconomic position on survival after oesophagectomy for cancer,13 14 where one showed no long-term survival advantage of higher socioeconomic position,13 while the other study showed a better short-term survival 14.…”
Section: Introductionmentioning
confidence: 99%
“…Education has been studied more extensively in relation to survival of other types of cancer,6–10 showing a beneficial effect of higher education on survival that might be explained by the differences in comorbidity burden, lifestyle factors, health awareness, adherence to treatment and healthcare seeking behaviour, factors which are also likely to influence the timing of referral and tumour stage at diagnosis 6–10. The impact of education on survival after oesophageal cancer diagnosis has been examined in cohort studies,3 11 12 but no clear associations were found. Two studies have evaluated the influence of the socioeconomic position on survival after oesophagectomy for cancer,13 14 where one showed no long-term survival advantage of higher socioeconomic position,13 while the other study showed a better short-term survival 14.…”
Section: Introductionmentioning
confidence: 99%
“…co-morbidity) or tumour factors and stage do not seem to fully explain socioeconomic inequalities[11-15]. Conversely, differences in healthcare may be responsible,[16] and, in some studies, no survival inequalities were observed when patients were treated in the same service setting[12,17,18]. However, overall, the evidence supporting any of the above explanations is limited[13].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, no clear association between survival and socioeconomic situation was found in Denmark, 26 as in six London boroughs 27 . Similarly, survival among patients in South‐East Wales (UK) diagnosed with esophageal carcinoma between 1998 and 2005 was not influenced by deprivation 28 . In Australia, absolute survival was not influenced by deprivation in patients living in New South Wales and diagnosed with esophageal adenocarcinoma between 1972 and 2005.…”
Section: Discussionmentioning
confidence: 97%